EXPLORATORY FACTOR ANALYSIS OF USER LOYALTY FACTORS IN LIVIN' BY MANDIRI MOBILE BANKING APPLICATION - Muhammad 'Athallah Hira Valensi; Ghea Sekar Palupi (Universitas Negeri Surabaya, 2026)
The rapid growth of digital banking in Indonesia, particularly mobile banking applications, has transformed consumer behavior in financial transactions. Livin' by Mandiri, Bank Mandiri's flagship mobile banking application, serves over 20 million active users. However, service disruptions such as login difficulties, transaction delays, and system instability have been reported, potentially affecting user satisfaction and loyalty. This study aims to identify the latent factors that shape user loyalty toward Livin' by Mandiri using Exploratory Factor Analysis (EFA). Data were collected from 100 active users in East Java through an online questionnaire measuring perceived usefulness, perceived ease of use, security and trust, user experience, system and service quality, and loyalty. The EFA results revealed four dominant factors with eigenvalues greater than 1.0: Usefulness and Behavioral Loyalty (eigenvalue=6.107, 33.9% variance), Ease of Use and Security-Trust (eigenvalue=1.447, 8.0% variance), System Performance and Service Reliability (eigenvalue=1.264, 7.0% variance), and User Experience (eigenvalue=1.123, 6.2% variance). These four factors collectively explained 55.1% of the total variance. After Promax rotation, the variance distribution became more balanced at 54.8%. The findings indicate that perceived usefulness integrated with behavioral loyalty is the most dominant factor, followed by ease of use combined with security perceptions. These results provide strategic insights for Bank Mandiri to enhance service quality, strengthen system stability, and maintain long-term user loyalty in a highly competitive digital banking landscape.